Disinfestation of Rhyzopertha dominica (F.) using microwave heat treatment to the Malaysian paddy - Manjur, Ahmed; Fareq, Malek, Dr.; R., Badlishah Ahmad, Assoc. Prof. Dr.; Md. Mostafijur, Rahman; Khairudi, Mohd Juni (World Academy of Science, Engineering and Technology (WASET), 2012)
Link to publisher's homepage at http://www.waset.org/